Analisis Persepsi Pengunjung Terhadap Infrastruktur Fungsi Sosial Taman Samarendah - Ayuni, Nur; Syafitri, Elin Diyah (SPECTA Journal of Technology, 2024)
The Mayor of Samarinda's Regulation Number 8 of 2018 regulates the Samarinda Smart City Masterplan, specifically within the Smart Society pillar. The work program outlined in the regulation aims to enhance environmental security and comfort, with the main goals of achieving security and public order stability and creating a conducive atmosphere. One of the key indicators of success for this program is a reduction in crime rates. One of the targets of the Samarinda City Masterplan is the enhancement of the social function of the Public Green Open Space at Taman Samarendah, with active community involvement being crucial as an instrument in the planning and development process. Therefore, this research was conducted to analyze visitors' perceptions using Importance Performance Analysis (IPA) regarding the park's social infrastructure. The study is qualitative, employing a rationalistic approach and utilizing 17 variables. The primary research method involved a survey by distributing questionnaires. The analysis found that certain facilities with high importance but low satisfaction ratings included gazebos, guard posts, toilets, swings, seesaws, slides, reading corners, and information boards. The findings of this research not only provide important input for authorities to formulate strategies for improving the quality of Public Green Open Spaces in Samarinda and emphasize the need for programs that increase public participation in managing public facilities. By involving the community actively, it is hoped that a sense of ownership and shared responsibility for public spaces will be fostered. Additionally, this research identifies unmet community needs, which can serve as a basis for developing more suitable facilities. Thus, Public Green Open Spaces can function optimally as social spaces that support community well-being, while also contributing to the overall goals of the master plan, including creating a safer and more comfortable environment for all citizens